IMPLEMENTASI ETIKA BISNIS ISLAM PADA PERILAKU PEDAGANG SAPI DI PASAR ROJOKOYO KEDIRI - Maulana, Muhamad Viki; Ersya Faraby, Muhammad (Universitas Negeri Surabaya, 2023)
Islamic business ethics is a standard of business ethics derived from the Quran and Hadith that must be followed by all business people. Doing business is not only aimed at seeking profit, but doing business must be based on ethics. As one of the places where business activities take place, Rojokoyo Animal Market is a cattle market center that is quite famous in the Kediri Regency area. This is because the number of traders is relatively large. Thus giving rise to several behaviors of cattle traders who are prone to cheating in trading. Thus, this study aims to determine the implementation of cattle trader behavior in buying and selling at Rojokoyo Market Kediri based on the perspective of Islamic business ethics. This research method is a descriptive qualitative method with a case study type of research. By using primary data and secondary data obtained by researchers from observations, interviews and documentation to several parties involved, as well as some literature in accordance with the research theme. While the results of this study show that all cattle traders in Rojokoyo Market have implemented the principles of Islamic business ethics.